A Revisit into the DEN2 NS2B/NS3 Virus Protease Homology Model: Structural Verification and Comparison with Crystal Structure of HCV NS3/4A and DEN2 NS3 - Y.K, Lee; Othman, Rozana; Wahab, Habibah A; Yusof, Rohana; Abd. Rahman, Noorsaadah (Malaysian Journal of Science, 2006)
Although the crystal structure of DEN2 NS3 serine protease has been reported, the proteolytic mechanism of this enzyme in the presence of NS2B as co-factor which greatly enhances its activity is not well-understood. Using the homology model of DEN2 NS3 co-complexed with NS2B co-factor based on HCV NS3/4A as the proposed template, the model of the DEN2 NS2B/3 complex was reproduced and its structure evaluated through PROCHECK, VERIFY3D and ERRAT. Comparison of the homology model with the crystal structure of DEN2 NS3 revealed that this homology model served as a better choice for the NS2B/3 protein model in drug design.